Myo-Inositol Levels in the Dorsal Hippocampus Serve as Glial Prognostic Marker of Mild Cognitive Impairment in Mice - Ebert, Tim; Heinz, Daniel E.; Almeida-Corrêa, Suellen; Cruz, Renata; Dethloff, Frederik; Stark, Tibor; Bajaj, Thomas; Maurel, Oriana M.; Ribeiro, Fabiola M.; Calcagnini, Silvio; Hafner, Kathrin; Gassen, Nils C.; et al. (Frontiers in Aging Neuroscience, 2021)
Dementia is a devastating age-related disorder. Its therapy would largely benefit from the identification of susceptible subjects at early, prodromal stages of the disease. To search for such prognostic markers of cognitive impairment, we studied spatial navigation in male BALBc vs. B6N mice in combination with in vivo magnetic resonance spectroscopy (1H-MRS). BALBc mice consistently showed higher escape latencies than B6N mice, both in the Water Cross Maze (WCM) and the Morris water maze (MWM). These performance deficits coincided with higher levels of myo-inositol (mIns) in the dorsal hippocampus before and after training. Subsequent biochemical analyses of hippocampal specimens by capillary immunodetection and liquid chromatography mass spectrometry-based (LC/MS) metabolomics revealed a higher abundance of glial markers (IBA-1, S100B, GFAP) as well as distinct alterations in metabolites including a decrease in vitamins (pantothenic acid, nicotinamide), neurotransmitters (acetylcholine), their metabolites (glutamine) and acetyl-L-carnitine. Supplementation of low abundant acetyl-L-carnitine via the drinking water, however, failed to revert the behavioural deficits shown by BALBc mice. Based on our data we suggest (i) BALBc mice as an animal model and (ii) hippocampal mIns levels as a prognostic marker of mild cognitive impairment (MCI), due to (iii) local changes in microglia and astrocyte activity, which may (iv) result in decreased concentrations of promnesic molecules.